Asymmetric Stepwise Reductive Amination of Aryl N‐Heteroaryl Ketones with Benzyl Amines via Iridium Catalysis. Issue 11 (30th September 2021) - Yang, Bing; Fu, Hao; Yuan, Jing; Wen, Simiaomiao; Wang, Chunqin; Liu, Qixing; Zhou, Haifeng
Abstract: An asymmetric reductive amination of aryl N‐heteroaryl ketones with Benzyl Amines has been realized via one‐pot two‐step process, using p‐toluenesulfonic acid and chiral iridium complexes as catalysts, a mixture of formic acid/triethylamine as a reductant. Twenty‐three examples of chiral aryl N‐heteroaryl methylamines were obtained with good yields and up to 99% ee. Abstract : Various chiral aryl N‐heteroaryl methylamines were prepared with good yields and up to 99% enantioselectivity via one‐pot stepwise ketimine formation/asymmetric transfer hydrogenation of aryl N‐heteroaryl ketones and benzyl amines.